Annie John - Kincaid, Jamaica 1949- (Farrar Straus Giroux, 1985)
Episodes from the young life of Annie John, aged 10 to 17, as she grows up on the Caribbean Island of Antigua. This is a magical coming-of-age tale, ripe with the special ambience of its tropical setting and sustained by Annie's far from naive awareness of the world around her. Death, illness, and poverty intrude on the narrator's perceptive sensibility from time to time, but even these experiences instruct her and expand her understanding of life and its shifting reality. Although Annie leaves Antigua at the end of the novel for a new role as a student in England, the hollowness she feels at her departure is balanced by the new self that awaits her as she begins the search for her own identity. A poetic and intensely moving work from the author of At the Bottom of the River.